The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1507/endocrj.42.341
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of a Malignant Epithelioid Hemangioendothelioma from Mouse Tnyroid Tumor.

Abstract: Abstract. A mouse epithelioid hemangioendothelioma (mEHE) cell line, passagable in vivo without TSH stimulation, was established from a thyroid tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Cell Culture-The mouse hemangioendothelioma (MHE) cell line established from the thyroid, expressing factor VIII and vimetidine (19), was used as vascular endothelial cells. MHE cells can incorporate acetylated low-density lipoprotein and stain positively for factor VIII antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture-The mouse hemangioendothelioma (MHE) cell line established from the thyroid, expressing factor VIII and vimetidine (19), was used as vascular endothelial cells. MHE cells can incorporate acetylated low-density lipoprotein and stain positively for factor VIII antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, concerning the molecular pathogenesis of primary thyroidal angiosarcomas, Hosoda et al (28) have recently reported on the establishment and characterization of a malignant angiosarcoma-like cell line, mEHE/CH5, which was derived from a mouse thyroid tumor and also overexpressed the proto-oncogene c-myc. Interestingly, the growth of these cells were thyrotropin (TSH)-independent, but could be inhibited by cAMP and vitamin D 3 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the growth of these cells were thyrotropin (TSH)-independent, but could be inhibited by cAMP and vitamin D 3 (28).…”
Section: Discussionmentioning
confidence: 99%